If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1 = 8 + -2x Reorder the terms: -1 + 4x = 8 + -2x Solving -1 + 4x = 8 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -1 + 4x + 2x = 8 + -2x + 2x Combine like terms: 4x + 2x = 6x -1 + 6x = 8 + -2x + 2x Combine like terms: -2x + 2x = 0 -1 + 6x = 8 + 0 -1 + 6x = 8 Add '1' to each side of the equation. -1 + 1 + 6x = 8 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = 8 + 1 6x = 8 + 1 Combine like terms: 8 + 1 = 9 6x = 9 Divide each side by '6'. x = 1.5 Simplifying x = 1.5
| 8+3q=11+2q | | -13=6-7 | | 2x-2=6x-4 | | 2x-4(x-3)=-9+5x-14 | | 3b+12-5b=22 | | 0.07-0.06(5x+4)=0.06x+0.13 | | 4x+13=-7x-30 | | 4x^2-26-14= | | 32m+54m+22=0 | | 6x-4x+20=-16 | | 2+3v=-6v-16 | | 3x+20+2(4x+4)=2x | | 26-(4x-11)=5(x+7) | | -(5z+1)=18 | | 4x+8-3x=14 | | 6x^3=5x^2 | | 3x+5.2=2-5y | | x+5=x+0 | | -13+7=-h-7+7 | | 3x-15=17-x | | 3(5y+2)-y=(2y-3) | | x=23-(-11) | | 8-3x=3x+2 | | 66=9x-13-8x+29 | | x/8+6=-12 | | 23-(-11)= | | w+(-9)=-4 | | 3x-15=3x | | 8x=6x-14 | | 2x-3=32 | | 15=5x-3(x+7) | | 4x-6=10x |